Two Cases of Benign Prostatic Hyperplasia with Bee Venom Pharmacopunture Therapy - Gang Hyeon Min; Kim Gwan Soo; Kim Doo Yong; Ryu Young Jin; Park Hee Soo; Ki Rok, Kwon (Korean Pharmacopuncture Institute, 2008)
Objective : The purpose of this study was to report the efficiency of Bee Venom Pharmacopunture Therapy by managering of Benign Prostatic Hyperplasia patients. Method : Two patients were treated with Bee Venom Pharmacopunture and another Korean Medicine therapy for six weeks and compared with I-PSS(International Prostate Symptom Score) before and after. Results : After treated with Bee Venom Pharmacopunture Therapy, 'I-PSS' values decreased significantly all the patients. Conclusions : Bee Venom Pharmacopunture Therapy was shown fairly effective to Benign Prostatic Hyperplasia.